Perbandingan Konstitusionalisme Indonesia dan Thailand: Analisis Kekosongan Penelitian pada Dinamika Pembatasan Kekuasaan Eksekutif - Eva Hudaevah; Dinda Nengsih Nurjaya; Rosy Uzmayanty; Fikri Hasan Fadhilah Noer; Ade Fartini (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
Constitutionalism plays a fundamental role in limiting state power and ensuring that government authority operates within ethical, legal, and democratic boundaries. Indonesia and Thailand offer two contrasting examples of constitutional development in Southeast Asia. Following the 1998 Reform era, Indonesia successfully strengthened mechanisms of checks and balances through the establishment of the Constitutional Court, decentralization reforms, and the empowerment of independent oversight bodies. In contrast, Thailand has experienced repeated cycles of military intervention, where post-coup constitutions have served not as tools to restrict state power, but rather as instruments legitimizing centralized authority and military dominance.This article synthesizes existing scholarly literature and identifies critical research gaps related to constitutionalism studies in both countries. First, there remains a scarcity of long-term empirical and quantitative studies assessing the effectiveness of constitutional limitations on executive, legislative, and judicial power. Second, current research has insufficiently examined informal political practices, including patronage networks, oligarchic influence, and military entrenchment within state institutions. Third, comparative constitutional studies covering the 2014–2025 period remain limited, particularly in assessing post-authoritarian and post-coup constitutional dynamics.The findings of this review highlight the need for deeper interdisciplinary research, integrating political science, legal studies, and institutional analysis to better understand the evolving nature of constitutionalism in Southeast Asia.